Penundaan Pemilihan Umum Menurut Sistem Hukum Indonesia - Delpedro Marhaen (Lex Renaissance, 2022)
The postponement of the 2024 General Elections, which was initiated by certain political elites some time ago, has received a negative response from the public through various protests. In fact, the issue of postponing the election has become a trending topic in the mass media and social media because apart from being considered undemocratic, it is also suspected that it does not have a strong legal basis, clear and unreasonable reasons as a condition for postponing an election. Based on these problems, this study examines whether postponing elections is possible in the Indonesian legal system? This is a normative juridical research with a statutory approach that examines legal materials of the 1945 Constitution of the Republic of Indonesia and Law no. 7 of 2017 on General Elections as amended by Government Regulation in lieu of the Law (Perpu) No. 1 of 2022. The results of this study indicate that the postponement of elections cannot be justified in the Indonesian legal system since the 1945 Constitution does not regulate the postponement of elections so that the postponement of the elections for 2024 which was rolled out by the political elite recently has no strong legal reasons and is not justified in the legal system Indonesia.Keywords: General Election, postponement, Constitution. AbstrakPenundaan Pemilihan Umum Tahun 2024 yang sempat digagas beberapa elite politik beberapa waktu lalu direspon secara negatif oleh publik melalui berbagai protes publik. Bahkan isu penundaan Pemilu ini menjadi trending topic di media massa dan media sosial sebab selain dinilai tidak demokratis, juga ditengarai tidak memiliki alas hukum yang kuat, jelas serta alasan yang tidak masuk akal sebagai syarat ditundanya sebuah penyelenggaraan Pemilu. Berdasarkan permasalahan tersebut, penelitian ini mengkaji apakah penundaan Pemilu dimungkinkan dalam sistem hukum Indonesia? Penelitian ini merupakan penelitian yuridis normatif dengan pendekatan perundang-undangan yang mengkaji bahan hukum berupa Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 dan Undang-Undang No. 7 Tahun 2017 tentang Pemilihan Umum sebagaimana telah diubah dengan Perpu No. 1 Tahun 2022. Hasil penelitian ini menunjukkan bahwa penundaan Pemilu tidak dapat dibenarkan dalam sistem hukum Indonesia sebab UUD 1945 tidak mengatur mengenai penundaan Pemilu sehingga penundaan Pemilu untuk tahun 2024 yang digulirkan elite politik belakangan ini tidak memiliki alasan hukum yang kuat dan tidak dibenarkan dalam sistem hukum Indonesia.Kata-kata Kunci: Pemilihan Umum, Penundaan, Konstitusi.